Students Engagement as A Predictor of Learning Satisfaction in A Synchronous Hybrid Learning Space - Wen-Wen Chua; Ying-Leh Ling (BIRCU, 2023)
This study focuses on the improvement of student engagement and learning satisfaction in synchronous hybrid learning spaces, which combine traditional on-site and online learning. While previous research has explored student engagement and learning satisfaction in on-site and online learning environments separately, there is a lack of literature investigating these factors in the context of synchronous hybrid learning. This study aims to fill this gap by examining the relationship between student engagements and learning satisfaction in synchronous hybrid learning spaces. A cross-sectional method was used to collect quantitative data from 169 students at a Technical and Vocational Education and Training (TVET) institution in Kuching, Sarawak. The study findings indicate that student engagement dimensions, including emotional, cognitive, and behavioral aspects, are predictive of learning satisfaction in both traditional on-site and online settings, as well as in synchronous hybrid learning spaces. These results have practical implications for the design and implementation of synchronous hybrid learning, providing valuable insights for educational practice and policy. By understanding and leveraging student engagement, educators and policymakers can enhance the effectiveness and value of synchronous hybrid learning environments.